Angular distribution of characteristic X-rays following electron impact ionization. (February 2023) - Pinheiro, Daniel; Amaro, Pedro; Machado, Jorge; Guerra, Mauro; Santos, José Paulo
Abstract: In this paper, we present a theoretical study of the X-ray fluorescence emission after vacancy of K-shell due to electron impact ionization. In particular, we focus on the angular distributions of the characteristic K α emission lines following this process. Rh was chosen for the analysis since it is a common element in X-ray tube anodes. In this analysis we also considered some elements along the period-4, i.e., Ni, Cu and Co as case-studies. In doing so, we studied the magnetic sub-level population of the ionized states, which is directly related to the angular distribution of the emission. A relative low angular distribution for the K α emission of Rh of 0.5% was observed, which makes the assumption of isotropic emission correct for most studies. Moreover, a comparison with the respective angular emission for adjacent elements in the fourth period of the periodic table shows that this isotropy is attributed to a small total angular momentum of the resulting configurations after ionization, as well as to opposite angular distributions of the various transitions, which average to a maximum of 0.7% angular asymmetry in Ni. Highlights: Evaluation of angular distribution of fluorescence lines after electron impact ionization. Fundamental parameters necessary for the fluorescence spectrum calculated with MCDF method. The element Rh, often used in X-ray tubes, together with the elements Ni, Co and Cu were used as case-studies. Observed small anisotropy traced-back to small alignment parameters, and the high density of lines.